The Influence of Ownership Concentration on Firm Resource Allocations to Employee Relations, External Social Actions, and Environmental Action - Crisóstomo, Vicente Lima (2015)
Objective – The purpose of this work is to examine the influence ofownership concentration on the funds allocated to CSR in Brazilian firm.Design/methodology/approach – Econometric models have beenestimated, with an index of CSR as the dependent variable, andownership concentration as the explanatory variable, together withrelevant control variables suggested in the literature (profitability,leverage, growth opportunities, and firm size). A Brazilian CSR databasehas been built using data extracted from two different sources, onerelative to CSR data and another that provides ownership structure andfinancial data. CSR policy is proxied by an index obtained as the ratiobetween funds directed to social action (employee relations, externalsocial actions, and environmental action) and net sales.Findings – The findings indicate that CSR is positively influenced byfirm ownership concentration in Brazil.Practical implications – The positive influence of ownershipconcentration on CSR may be an indication that large controllingshareholders of Brazilian firm may be considering CSR as an effectiveway to improve the image and reputation of the firm and its owners. Thisbelief may be stimulating CSR projects and their disclosure in Brazil.Originality/value – This work is an additional contribution to thedebate about the role played by ownership structure on CSR. Takinginto account that the central point of Stakeholder Theory is a firm’sconcern with all its stakeholders, the research builds on Stakeholderand Agency Theories by assessing the influence of large controllingshareholders on a firm’s social concerns.